An Integrated Green Management Model for Fashion SME Sustainability: Moderating Role of Green Culture Using PLS-SEM - Siti Sumiati; Sri Dewi Wahyundaru; Sri Wahyuni; Caroline Caroline; Sekar Langit Nugraheni (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Organizational green culture as a moderating role in sustainable fashion SMEs. An environmentally friendly strategy is fundamental for the survival of fashion SMEs in emerging industries. Fashion SMEs in Central Java are under considerable environmental pressure; however, little research has examined the integrative role of organizational green culture as a moderator. Objective: This study aims to investigate the impact of green knowledge management and green innovation on SME sustainability and to evaluate green culture as a moderator. Methods: The research model was designed using online questionnaires and SmartPLS, where the samples were selected using stratified random sampling, consisting of 150 fashion SMEs from six regencies in Central Java. Five direct hypotheses and two moderating hypotheses were tested using PLS-SEM with bootstrapping (n = 500 resamples). Results: The findings show that green innovation mediates the relationship between green knowledge management and sustainability, while green culture moderates the effect of green knowledge management. Green knowledge management significantly influences SME sustainability (β = 0.103, p = 0.003) and green innovation (β = 0.093, p = 0.000). Organizational green culture significantly moderates the relationship between green knowledge management and green innovation (p = 0.016), as well as the relationship between green knowledge management and sustainability (p = 0.020). Conclusion: This study provides empirical evidence that organizational green culture is a key factor in improving environmentally friendly knowledge sharing and innovative decision-making effectiveness to support equitable sustainable development for fashion SMEs in developing countries.